(untitled) (Journal of Contemporary Philology, 2018)
This article’s objective is to conduct a critical discourse analysis of political speeches in the Republic of Macedonia and the USA. This research gives an insight into the manipulative function of language and it shows how politicians achieve this manipulation. For this purpose, eight political speeches have been analyzed: four speeches given by Macedonian politicians (Gruevski, Zaev, Ivanov, and Pendarovski) and four given by American politicians (Obama, Romney, Bush, and Kerry). The analysis covers the pragmatic aspect, it examines how much attention the politicians pay toexpressing their own opinion and political stances and how they include the audience in their speech. The focus of the analysis is on the personal pronouns.